Diamond lattice Heisenberg antiferromagnet. (16th March 2018) - Oitmaa, J
Abstract: We investigate ground-state and high-temperature properties of the nearest-neighbour Heisenberg antiferromagnet on the three-dimensional diamond lattice, using series expansion methods. The ground-state energy and magnetization, as well as the magnon spectrum, are calculated and found to be in good agreement with first-order spin-wave theory, with a quantum renormalization factor of about 1.13. High-temperature series are derived for the free energy, and physical and staggered susceptibilities for spin S   =  1/2, 1 and 3/2, and analysed to obtain the corresponding Curie and Néel temperatures.